TEACHING WRITING BY USING GENRE BASED APPROACH (GBA) AT SMAN 2 PUJUT - Riska Juanda Maharani; Muhammad Muhlisin; Ahmad Hanan (Sinar Lima, 2025)
At SMAN 2 Pujut, initial observations revealed that students in Grade XI MIPA had difficulty in organizing ideas, applying appropriate language features, and understanding the structure of specific text types—especially expository texts. This highlights the need for a more systematic approach to writing instruction that not only focuses on grammar but also introduces students to text organization and genre awareness. This study aims to investigate the effect of using the Genre-Based Approach (GBA) in teaching writing to Grade XI MIPA students at SMAN 2 Pujut. GBA is a pedagogical model that focuses on understanding text structures based on specific genres and the social context of the texts. Using a pre-experimental method with a one-group pre-test and post-test design, 25 students were assessed before and after a GBA-based writing intervention. Although there was an increase in the students’ average writing scores, statistical analysis using a paired t-test (p = 0.22 > 0.05) showed no significant improvement. Despite this, GBA positively contributed to students’ organization and clarity in writing. It is recommended that future studies incorporate more varied strategies and address motivational and environmental factors.